Akuntabilitas Pengelolaan Dana Desa: Studi Kecamatan Losari - Putra, Romy Dwi; Agung Santoso, R. Ery; Nurcahyono, Nurcahyono (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
The purpose of this study was to analyze the influence of the competence of village fund managers, internal control systems, community participation, the use of information technology on the accountability of village fund management. The sampling method used simple random sampling with a sample size of 50 village officials in villages throughout Losari District, Cirebon Regency. This study uses an analytical method with the Partial Least Square (PLS) approach using the WarpPLS software. The results showed that the competence of village fund managers, internal control systems, community participation had a positive effect on the accountability of village fund managers, while the use of information technology had a negative effect on the accountability of village fund management.